2007
DOI: 10.1002/bit.21521
|View full text |Cite
|
Sign up to set email alerts
|

A new process for the continuous production of succinic acid from glucose at high yield, titer, and productivity

Abstract: A novel three stages continuous fermentation process for the bioproduction of succinic acid at high concentration, productivity and yield using A. succiniciproducens was developed. This process combined an integrated membrane-bioreactor-electrodialysis system. An energetic characterization of A. succiniciproducens during anaerobic cultured in a cell recycle bioreactor was done first. The very low value of Y(ATP) obtained suggests that an ATP dependent mechanism of succinate export is present in A. succinicipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 25 publications
(25 reference statements)
0
85
0
2
Order By: Relevance
“…Lee et al [19] reported a maximum succinic acid yield of 0.91 mol/mol and a maximum productivity of 1.8 gL -1 h -1 . Meynial-Salles et al [23] observed growth inhibition caused by the endproducts, succinic acid and acetic acid. The introduction of a coupled mono-polar electrodialysis for removing the end products from the fermentation broth enhanced growth, productivity, and final product concentration.…”
Section: Natural Overproducersmentioning
confidence: 99%
“…Lee et al [19] reported a maximum succinic acid yield of 0.91 mol/mol and a maximum productivity of 1.8 gL -1 h -1 . Meynial-Salles et al [23] observed growth inhibition caused by the endproducts, succinic acid and acetic acid. The introduction of a coupled mono-polar electrodialysis for removing the end products from the fermentation broth enhanced growth, productivity, and final product concentration.…”
Section: Natural Overproducersmentioning
confidence: 99%
“…With the exception of the work done by Urbance et al [11] and Meynial-Salles et al [12], all continuous SA work was done at the Korean Institute of Advanced Technology (KAIST) where M.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from normal suspended cell systems ('chemostat'), membrane systems with cell recycle as well as biofilm reactors were used in an attempt to enhance productivity [11][12][13]17]. Particular success was achieved by Meynial-Salles et al [12] with A. succiniciproducens where a very high productivity of 14.8 g L -1 h -1 was obtained with a SA yield of 0.83 g g -1…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of production conditions and/or manipulation of metabolic pathways led to the development of succinate production processes with high yield (Ͼ1 mol/mol glucose) and productivity (14,31,34,35). However, most of the described strains require complex medium and show high by-product accumulation (mainly pyruvate and acetate), increasing the costs associated with production and purification.…”
mentioning
confidence: 99%